Recruitment of some respiratory muscles during three maximal inspiratory manoeuvres. - Nava, S (1993)
BACKGROUND--A study was undertaken to determine the level of recruitment of the muscles used in the generation of respiratory muscle force, and to ascertain whether maximal diaphragmatic force and maximal inspiratory muscle force need to be measured by separate tests. The level of activity of three inspiratory muscles and one expiratory muscle during three maximal respiratory manoeuvres was studied: (1) maximal inspiration against a closed airway (Muller manoeuvre or maximal inspiratory pressure (MIP)); (2) maximal inspired manoeuvre followed by a maximal expiratory effort (combined manoeuvre); and (3) maximal inspiratory sniff through the nose (sniff manoeuvre). METHODS--All the manoeuvres were performed from functional residual capacity. The gastric (PGA) and oesophageal (POES) pressures and their difference, transdiaphragmatic pressure (PDI), and the integrated EMG activity of the diaphragm (EDI), the sternomastoid (ESTR), the intercostal parasternals (ERIC), and the rectus abdominis muscles (ERA) were recorded. RESULTS--Mean (SD) PDI values for the Muller, combined, and sniff manoeuvres were: 127.6 (19.4), 162.7 (22.2), and 136.6 (24.8) cm H2O, respectively. The pattern of rib cage muscle recruitment (POES/PDI) was similar for the Muller and sniff manoeuvres (88% and 80% respectively), and was 58% in the combined manoeuvre, confirming data previously reported in the literature. Peak EDI amplitude was greater during the sniff manoeuvre in all subjects (100%) than during the combined (88.1%) and Muller (61.1%) manoeuvres. ESTR and EIC were more active in the Muller and the sniff manoeuvres. The contribution of the expiratory muscle (ERA) to the three manoeuvres was 100% in the combined, 26.1% for the sniff, and 11.5% for the Muller manoeuvre. CONCLUSIONS--Each of these three manoeuvres results in different mechanisms of inspiratory and expiratory muscle activation and the intrathoracic and intra-abdominal pressures generated are a reflection of the interaction between the various muscle groups. The Muller and sniff manoeuvres reflect mainly the force of the inspiratory muscles and the combined manoeuvre that of the diaphragm.